A systematic literature review on electricity management systems. (September 2015) - Rasool, Ghulam; Ehsan, Farrukh; Shahbaz, Muhammad
Abstract: Many countries in the world and most importantly Pakistan is suffering from severe electricity crisis. Information Technology (IT) is being used in every field of the life and we may apply IT to overcome electricity crisis. A large number of papers are presented by different researchers on electricity management. The key motivation of this systematic literature review is to study, analyze and explore the status of different solutions presented for management of electricity throughout the world and determine requirements for the development of a new electricity management system. We apply standard systematic review method with the manual search of three digital libraries. Out of 74 primary studies, 27 studies are software contributions, 13 studies are hardware solutions, 18 studies represent the theoretical work and 16 studies contribute proposed ideas. The quality of the contributions is fair as 74 articles out of 209 were selected as candidate studies after manual peer review. Currently, the solutions presented by different researchers are limited in scope. Many researchers are working on tool contributions, but most of them are only providing solutions for specific regions and communities. There is a need to develop a generic Electricity Management System (EMS) that should be customizable and can be used as generic solution.